Extractive industry a burden or an opportunity for sustainable development? - SHTIZA, Aurela (European Journal of Sustainable Development, 2013)
The shortage of raw materials in global markets and the sky rocketing of commodityprices, have induced European authorities to take initiatives to improve innovation inEurope by creating the European Innovation Partnership on Raw Materials (2012) and make inventory of the existing European raw materials. Albania is a rich country in natural raw materials, such as chromium, copper, ferronickel, coal, bitumen as well ascrude oil which might supply primary and secondary raw materials for some of the European needs. This literature review discusses the role of the Albanian institutions, the natural resources industry, potential investors and stakeholders in order to provide a setof indicators and platforms that can help to develop the extractive industry in Albania and monitor amelioration within sustainable development principles. A map with the potential prospects of the natural resources will be a first step in identifying the further potential for exploitation. Mineral resource policies and governance, sustainable processing and supply chain as well as environmental management information system (EMIS) are some of the crucial tools identified, which will help to set up the indicators and quantify the achievements in environmental management in Albania. Moreover, the integration of practices that will support institutional capacity building; follow-up practices; the mainstreaming of global environment into planning; and the compliance monitoring process will additionally improve the environmental situation in Albania. Aligning business strategy with environmental policy, socio-economic analysis, environmental auditing are decisive tools in order to provide the Albanian authorities with a clear overview of the economic costs and the social benefits for sustainable development of the extractive sector in Albania.